Analisis Efisiensi Penggunaan Input Produksi pada Usahatani Bawang Merah di Desa Songan B, Kecamatan Kintamani,Kabupaten Bangli - WIDIAWATI, WIDIAWATI; SARJANA, I DEWA GEDE RAKA; DJELANTIK, A.A.A WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.3, Juli 2019, 2019)
Efficiency Analysis of the Use of Production Input on Shallot Farming in Songan B Village, Kintamani Sub-District, of Bangli Regency Bali is a tourism area and a potential market for shallot business. One of the shallot production centers in Bali is Songan B Village, Kintamani Sub-District, Bangli Regency. Fluctuating shallot production is thought to be due to the inefficient use of production inputs so that it is needed to analyze the efficiency of the use of production inputs. This study aims to determine the effect and efficiency of the use of shallot production inputs. The study was conducted in Songan B Village by analyzing production inputs such as area of arable land, seeds, manure, NPK fertilizer, solid pesticides, liquid pesticides and labor by using the Cobb-Douglas production function.The data used were data in the March, April, and May planting season of 48 respondents determined by a simple random method. Efficiency can be seen from the comparison of marginal production values and production input prices. The results showed that the area of cultivated land, NPK fertilizer and labor had a positive effect on the shallot production. Solid pesticides negatively affected the shallot production, while the seeds, manure and liquid pesticides had no significant effect. The inefficient use of production inputs is the area of cultivated land and NPK fertilizer, so that its use must be increased, while other production inputs are inefficient that their uses must be reduced.